Pemanfaatan Digital Marketing Dalam Strategi Pemasaran Produk Kerajinan Ecoprint Di Kepanjenlor Kota Blitar - Anindita Vella Puspitasari; Jojok Dwiridotjahjono (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
The use of the internet in the era of the industrial revolution 4.0 is currently accompanied by technological developments that are experiencing very rapid changes so that the information obtained is quite easy and very fast to get the desired information. The marketing and sales system is no exception, which is growing and consumer demands are increasingly complex. Digital marketing is one of the marketing or promotional media strategies that currently has a major influence on sales. MSMEs Ecoprint Crafts is a production and buying and selling business of ecoprint crafts in Kepanjenlor, Blitar city. In this case, MSMEs players still have problems with the development of business and sales strategies. Through the use of digital marketing, it is hoped that it will be able to help Ecoprint Craft MSMEs actors, as one of the promotional media for developing a business. The method used in this research is to use a qualitative method with a descriptive approach. As well as using the mentoring method by carrying out several stages, namely, observation, planning, implementation, and evaluation of each step taken. In the data collection stage on ecoprint craft MSMEs by using direct interviews with ecoprint craft MSMEs owners. From the results of this study it results that by choosing social media as the right promotional media.